Sosialisasi Penggunaan Media Sosial Tik Tok DI SDN 13 Lolong Kota Padang - Efendi, Nofriza; Wati, Lesma; Prananda, Gingga; Barkara, Refli Surya (Jurnal Masyarakat Mengabdi Nusantara, 2024)
This study examines approaches to social media use of TikTok in elementary schools, focusing on safety, education, and positive impact. In an increasingly digitally connected environment, children face increased opportunities and risks associated with social media use. The aim of this study is to develop appropriate approach strategies to help students understand how to use her TikTok in a balanced and safe manner. Research methods include literature research on children's social media use and analysis of educational policies related to social media in elementary schools.The results demonstrate the need for educational approaches that focus on positive creativity, digital awareness, and online safety. The proposed approach includes educational sessions, workshops, and training sessions involving students, teachers, and parents. Public relations takes into account age restrictions, privacy settings, and the positive and negative effects of online activity.  The role of teachers and school staff in monitoring and supporting students in the digital world will also be strengthened. The implementation of this outreach strategy aims to create a supportive, educational and safe environment for the u. se of the social media TikTok among primary school children, thereby bridging the gap between technological development and child protection